Certain Issues Related to Annulment of Final Court Decisions According to the Civil Procedure Legislation - Peranidze, Irma (European Scientific Journal, ESJ, 2017)
The Civil Procedure Code of Georgia is a codified normative act which meticulously defines the general principles of the legal procedure, the court’s departmental subordination and judgment, the parties participating in process, their legal capacity, proceedings at all instances of the court, appeals of court decisions, etc. Generally, norms of procedural law are of imperative character. Participants (parties) of these legal relations do not have right to transform or change them. In other words, participants (parties) of formal relations are equipped with only those rights and obligations that are imposed on them only by the legislation or the court practice. Thus, exactly the procedural law determines the degree of democracy and freedom of the state legal system. It does not matter how broad an individual’s rights are; these rights lose sense if they are not protected and realized by the state enforcement mechanisms. That is why, when disputes concerning infringement of the Article 6 of the European Convention on Human Rights arise, the European Court of Human Rights always examines whether the applicant’s formal procedural rights are protected and how the rights recognized by the national legislation are in line with the standards of human rights.